Conformational analysis of peptides derived from the BRI gene. Issue 3 (2001) - Lelyveld Lelyveld, Victor Victor; El‒Agnaf El‒Agnaf, Omar Omar; Siligardi Siligardi, Giuliano Giuliano; Hussain Hussain, Rohana Rohana; Haris Haris, Parvez I. Parvez I.; Lee Lee, Maria Maria; Austen Austen, Brian Brian
Abstract : The 34-residue peptides (ABri and ADan) derived from the 3′ end of the gene BRI which is mutated in British and Danish families with dementia, have been synthesized, with and without the predicted intramolecular disulphides. CD measurements show that the oxidised and reduced forms have tendencies to adopt β ‒structure at neutral pH with prolonged time of incubation. The shift to β ‒structure is accompanied by oligomer formation. The neurotoxic properties of these oligomers in vitro may explain the cognitive decline seen in the patients. Structural analyses will be useful in the design of therapeutic drugs.